CORRELATES OF HUMAN RESOURCE DEVELOPMENT AND SEAPORT PERFORMANCE IN NIGERIA - Bello K.; Ogola D.B.; Mogbojuri O. (International Journal of Maritime and Interdisciplinary Research, 2024)
This study analysed the relationship between human resource development and its influence on selected seaports in Nigeria. It examined the various factors used to motivate employees at the selected seaports which includeLagos Port Complex, Tincan Island Port Complex, Onne Port Complex, and Delta Port Complex. Questionnaires and interview of major employers of the selected terminal operators were the instrument of data collection. The data were collected through questionnaires and interviews from the terminal operators. The pearson product moment correlation coefficient was used to determine the strength of relationships between port performance and human resource development. Furthermore, descriptive statistics were employed to explain the motivational elements for employees. According to the findings, there is a positive correlation between human resource development and the performance of all seaport terminals at various levels. Wages incentives, discounts on imported commodities provided by terminal operators, payment of house allowance, holiday, and availability of transportation for simple conveyance of personnel are the most important factors that impact maritime workers, in descending order. In conclusion, terminal operators will profit greatly if they provide training and development programme for their employees, and should consider modalities for remuneration and employee welfare that will make them feel content in their job.
This study analysed the relationship between human resource development and its influence on selected seaports in Nigeria. It examined the various factors used to motivate employees at the selected seaports which includeLagos Port Complex, Tincan Island Port Complex, Onne Port Complex, and Delta Port Complex.
Keywords: Human Resource Development; Terminal operators; Seaport; Performance; Nigeria